Penggunaan Media Sosial Berbasis Digital Dalam Pembelajaran Bahasa Indonesia Berorientasi Deep Learning Bagi Guru SD - Rahmawati, Evi; Heryani, Rina; Heryanto, Dwi; Hartati, Tatat; Mulyasari, Effy; Prasetyo, Rifki Gagak Bayu; Sabilah, Nur Syahrin; Sakti, Yuda Candra (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
This Community Service Program as motivated by the lack of teacher training and professional development. Many teachers do not have the opportunity to participate in regular training or professional development programs. As a result, many of them face difficulties in adopting more modern and effective teaching methods or technologies. The purpose of this Community Service Program is to improve teachers’ ability to develop and use effective learning media that align with students’ needs and interests. The method used in this community service program activity is socialization (delivering materials) and training for teachers on the use of digital-based social media in teaching Indonesian language with a deep learning orientation for elementary school teachers in Garut Regency, particularly those who are partners of the Primary School Teacher Education Study Program. The results of this Community Service Program indicate that elementary school teachers in Garut Regency are capable of developing and using digital-based social media in teaching Indonesian language with a deep learning approach. This training successfully enhanced teachers’ abilities to utilize social media as an innovative and interactive learning medium.